Glucocorticoid Exposure Induces Preeclampsia via DampeningLipoxin A4, an Endogenous Anti-Inflammatory and Proresolving Mediator - Liu, Haojing; Huang, Wei; Chen, Liping; Xu, Qiang; Ye, Duyun; Zhang, Dongxin (Frontiers in Pharmacology, 2020)
The pathogenesis of preeclampsia (PE) involves several pathophysiological processes that may be affected by glucocorticoid (GC). We confirmed previously that GC exposure could result in PE, while PE is linked to a deficiency of lipoxin A4 (LXA4), an endogenous dual anti-inflammatory and proresolving mediator. The present study was to investigate whether GC exposure induces PE via dampening LXA4. In the study, cortisol levels of PE women were higher than those of normal pregnancies, LXA4 levels were downregulated in both PE patients and GC-mediated PE rats, and leukotriene B4 (LTB4) levels were upregulated in both PE patients and GC- mediated PE rats. Moreover, cortisol levels were negatively correlated to LXA4 levels, while positively correlated to LTB4 levels in PE patients. Mechanically, GC downregulated LXA4via disturbing its biosynthetic enzymes, including ALOX15, ALOX5B and ALOX5, especially activating ALOX5, the key enzyme for class switching between LXA4 and LTB4. Importantly, replenishing LXA4 could ameliorate PE-related symptoms and placental oxidative stress in PE rat model induced by GC. Moreover, LXA4 could inhibit GC-mediated ALOX5 activation and LTB4 increase, and also suppress 11β-HSD2 expression and corticosterone upregulation. The protective actions of LXA4 might be explained by its roles in antagonizing the adverse effects of GC on trophoblast development. Together, our findings indicate that GC exposure could contribute to PE through dampening LXA4, and GC/LXA4 axis may represent a common pathway through which PE occurs.